Evaluation of growth performance and litter size of four different crossbred sheep in Bangladesh Livestock Research Institute (Bangladesh Journal of Livestock Research, 2021)
The purpose of the experiment was to investigate the litter size and growth performance of four distinct crossbred sheep at Bangladesh Livestock Research Institute (BLRI). Data were obtained on 160 crossbred sheep of Dorper, Perendale, Suffolk, and Damara raised on BLRI sheep research farm, Savar, Dhaka, from January 2021 to June 2022. The effects of genotype, sex, and season on birth weight (Bwt), 3 months body weight (Bwt3m), 6 months body weight (Bwt6m), 12 months body weight (Bwt12m), average daily gain from birth to 3 month (ADG3m), 3 to 6 month (ADG6m), and 6 to 12 month (ADG12m) of ages and litter size (LS) of doe were investigated. All the data in this study were analyzed by the Statistical Package for the Social Sciences (SPSS) version 20.0 computer program and the significance differences among the mean values were ascertained using Duncan's multiple range test (DMRT). The effect of genotype on Bwt6m was found highly significant p